The Role Of The Indigenous Knowledge System Of The Community Model Intergovernmental Cooperation In Education Program Guide In The Province Of South Sulawesi - Suryadi Lambali (Iapa Proceedings Conference, 2018)
Noting the fact that the index of the quality of primary and secondary education in the province of South Sulawesi, which was ranked 21 out of 34 provinces that exist throughout Indonesia (2009), the South Sulawesi provisional government is determined to improve the quality of education index to rank 10 (2013). To support these policies then issued Regional Regulation No. 4 of 2009 concerning free education program which was further supplemented by the Governor Regulation No. 4 of 2011 on the implementation of the free education program. The program is held by a model of cooperation between the provincial government and the government district /city in South Sulawesi. Particularly in relation to the distribution of the proportion of the budget given for each level of government. It was agreed that the provincial government issued a budget of 40% and district / municipal governments 60%. In the implementation until 2016 (approximately 8 years) has not shown a significant index of the quality of education, because it is still ranked 19. The objective of this study is to analyze why the model of cooperation among government used in its free education program has not been effective. To achieve these objectives, the research approach used is qualitative types of cases. The results showed that the model of intergovernmental cooperation that is used is politics society and politics of inter-organization and not used of legal and administrative approaches.